Executive functions and Social Cognition in adolescents in the context of Bullying - Barceló, Ernesto (2023)
Bullying is a contemporary social phenomenon that impacts multiple social structures and contexts. This study aimed to establish the association between executive functions (EF) and social cognition in adolescents. A cross-sectional descriptive study with a sample of 109 subjects was selected by convenience sampling. Multinomial logistic regression was performed, finding that social cognition is a protective factor (OR: 0.17 IC 95% 0.05-0.59) (OR: 0.27 IC 95% 0.08- 0.85) in the group of aggressors to controls; in addition, the group of victims to controls (OR: 0.15 IC 95% 0.05 – 0.42) (OR: 0.30 IC 95% (0.11- 0.82). Thus, adequate social cognition is associated as a protective factor against bullying, and presenting deficits in EF is associated with a threefold increased risk of bullying.